Efisiensi Jumlah Tenaga Kerja pada Penerapan New Normal di CV X - Sharon Natashya Sutanto; Debora Anne Yang Aysia (Jurnal Titra, 2021)
CV X is a printing company. CV X has 2 types of business, which is offset and digital, but this research focus more on the production department in the offset section of CV X. The COVID-19 pandemic has decreased the demand of printing, therefore, CV X must make some adjustments to the number of workers so that the number of workers are still efficient. Currently, the number of workers in production department are 22 workers. The improvement of work standards are made based on observations and job descriptions of each worker by considering production capacity and physical distancing health protocols. Determining the optimal number of workers in some demand conditions are done using Macro Excel and done by minding the production capacity and limits on the number of people in one workspace according to WHO recommendations. Application of Macro Excel program is done by counting 2 examples of existing cases. The first example has demand percentage of 77.05% and the optimal number of worker is 17 workers and the second example has demand percentage of 13.02% and the optimal number of worker is 12 workers. The results of the Macro Excel are in accordance with physical distancing health protocols.